Building ocean acidification research and policy capacity in the wider Caribbean region: a case study for advancing regional resilience - Kalina C. Grabb; Natalie Lord; Kerri L. Dobson; Debbie-Ann D. S. Gordon-Smith; Elva Escobar-Briones; Marcia Creary Ford; Sylvia Lander; Gabriella D. Kitch; Melissa Meléndez; Julio Morell; Alain Muñoz Caravaca; Jan Newton; et al. (Frontiers in Marine Science)
To meet scientific, policy, and community goals, there is a critical need to strengthen research capacity, increase monitoring, and inform adaptation and mitigation policies to enhance resilience against ocean acidification (OA) and associated multi-stressors in the Caribbean. In 2023, an OA Needs Based Assessment survey of ocean professionals was conducted, engaging 59 participants from across the wider Caribbean to evaluate regional challenges and opportunities in OA research and monitoring. To understand differences in OA research capacity related to training and funding, we divide the respondents into four groups: those that have received 1) training and funding, 2) training only, 3) funding only, and 4) neither training nor funding. Results indicate regional strengths include awareness of local oceanic conditions, access to nearshore sites, and strong social support networks in ocean research. Regional barriers include limited technical capacity and funding to conduct oceanographic research and monitoring, and in particular, carbonate measurements. The four training and funding groups vary significantly, suggesting that access to training and funding are important factors to increasing the amount of access that respondents have to different types of equipment, the number of different types of measurements they conduct, the number of different habitats they research, and the amount of experience they have conducting OA research. This study also demonstrates the community-led efforts to address local OA challenges by presenting a case study on the formation of the Global Ocean Acidification Network (GOA-ON) OA Caribbean Hub that was founded by local leaders (co-authors of this study) who were inspired through the survey process and engagement that was conducted by co-authors. This study provides examples of avenues and challenges to build OA capacity for research and monitoring from the ground up within the wider Caribbean to advance towards global sustainability goals.